Topical application of povidone-iodine/dimethylsulfoxide ophthalmic gel preparation in Dutch-Belted rabbits. (3rd July 2019) - Pelletier, Jesse S.; Devine, John; Capriotti, Kara; Barone, Samuel B.; Capriotti, Joseph A.
Abstract: Purpose: To determine the ocular and systemic toxicity of a novel, topically applied ophthalmic gel preparation of povidone-iodine (PVP-I) and dimethylsulfoxide (DMSO) in Dutch-Belted rabbits. Materials and Methods: Rabbits were administered doses of the test material or control by ocular instillation four times/eye/day, 7 d/week, for a minimum of 14 consecutive days. Dosing consisted of instillation of 50 µl of the appropriate test material solution or control material (saline) into each eye of the rabbit. On the last dose of the day, 250 µl of the appropriate test material solution or control material was applied to the eyelids of each eye. Results: Treatment-related clinical signs observed during the study were limited to mild non-inflammatory changes to the eyelids and eyelashes. There was no associated pathology upon histological examination of ocular or systemic tissues. Body weights and body weight gains were unaffected by treatment. Evaluation of clinical pathology profiles (haematology, coagulation, and clinical chemistry) did not reveal any test article-related toxicity and there were no macroscopic or microscopic findings at the terminal sacrifice. Conclusions: The compositions studied in the present investigation were developed to enable repeat-dosed application to the ocular surface and periocular skin surfaces without ocular, skin or systemic toxicity. The PVP-I/DMSO compositions tested did not cause any toxicity to the ocular surface or the periocular skin. Systemic toxicity from the preparations under study was not observed in any histological or gross pathological examination.